For real x , find the maximum value of 3 x 2 + 9 x + 7 3 x 2 + 9 x + 1 7 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Minimum value can be directly taken as -D/4a which gives 1/4 and hence required max value=1+40=41
another way is to write it in form of a perfect square +something.still,nice solution
Wait!I tried 41 yesterday and it showed it's incorrect?How?
Log in to reply
That was same question with wrong answer.
Used calculus. But your classical approach seems better.
Let the expression be f ( x ) , then we have:
f ( x ) = 3 x 2 + 9 x + 7 3 x 2 + 9 x + 1 7 = 1 + 3 x 2 + 9 x + 7 1 0 = 1 + 3 ( x 2 + 3 x + 4 9 ) + 4 1 1 0 = 1 + 3 ( x + 2 3 ) 2 + 4 1 1 0
f ( x ) is maximum, when 3 ( x + 2 3 ) 2 + 4 1 is minimum. Since 3 ( x + 2 3 ) 2 ≥ 0 , 3 ( x + 2 3 ) 2 + 4 1 is minimum, when 3 ( x + 2 3 ) 2 = 0 .
Therefore, maximum f ( x ) = 1 + 0 + 4 1 1 0 = 1 + 4 0 = 4 1
Easily solvable with calculus. set f(x) = the expression. compute the derivative of the function, which is
f'(x)= (-60x-90)/(3x^2+9x+7)^2 -60x-90=0 x=-3/2 is a critical point.
You can plug in the point x=-3/2 to make sure it's continuous there, but it's pretty obvious by looking at it. Find a number smaller than -3/2 to test for f((x<-3/2)) > 0.
f(-2) = 11 >0, so that means x=-3/2 is a maximum. You can confirm by plugging in values of x < -3/2 to see that they are smaller than f(-3/2) = 41.
Problem Loading...
Note Loading...
Set Loading...
= 3 x 2 + 9 x + 7 3 x 2 + 9 x + 1 7 = 3 x 2 + 9 x + 7 3 x 2 + 9 x + 7 + 1 0 = 1 + 3 x 2 + 9 x + 7 1 0
Now for the above expression to get maximum value, the value of 3 x 2 + 9 x + 7 must be minimum.
The minimum value of a 3 x 2 + b 9 x + c 7 would be at x = − 2 a b = − 6 9 = − 2 3 .
So maximum value of f ( x ) ,
= 1 + 3 x 2 + 9 x + 7 1 0 = 1 + 3 ( − 2 3 ) 2 + 9 ( − 2 3 ) + 7 1 0 = 1 + 4 1 1 0 = 1 + 4 0 = 4 1